CULTIVATE ANTI-CORRUPTION IN ANTI-CORRUPTION MANAGEMENT IN INDONESIA - Nuravoy Sihotang; Ilham Septiani; Fatih Haramain; Febri Damayanti; May Riski Anita Rahayu; Arifin, Afief (Fakultas Hukum Universitas Djuanda, 2023)
Eradication or covercoming of corruption in the modern is marked by the birth of a new institution called the kpk,because government institutions called the kpk.based on law number of the 2002 concerning the kpk,becaous government institutions that handle corruptions cases have not functioned efficiently,kpk with all the functions and authorities given by law has worked and succeded in dismantling large cases of corruption within government agencies that have been affordable by law enforcement.anti corruptions values and attitudes are needed in society so that anti corruption countermeasures are effective anda efficient,kpk must also cooperate all components of society such as;NGOS,the press and public figures in cultivating the anti corruption movement in the context of anti corruption prevention in Indonesia. The mode of corruption that used to be just’’greetings’’is how becoming more sophisticated as technology develops